Corn Residue Baling and Grazing Impacts on Soil Carbon Stocks and Other Properties on a Haplustoll. Issue 1 (18th January 2018) - Ruis, Sabrina; Blanco-Canqui, Humberto; Burr, Chuck; Olson, Brian; Reiman, Mark; Rudnick, Daran; Drijber, Rhae; Shaver, Tim
Abstract : Core Ideas: Corn residue baling reduced SOC stocks by 2.16 Mg ha –1 yr –1 compared with no removal after 3 yr. Baling increased erosion potential and reduced soil microbial biomass. Cattle grazing of corn residues did not generally affect soil properties. Baling and grazing effects on soil properties did not vary with irrigation and tillage system. Baling affected soil properties more than grazing regardless of irrigation and tillage. Baling and grazing of corn ( Zea mays L.) residues are common practices in irrigated systems to meet the increasing demand for forage. Our understanding of how such practices affect soil properties under different tillage and irrigation levels is, however, still limited. This study assessed the impacts of corn residue baling and grazing on soil organic C (SOC) stocks, particulate organic matter (POM) concentration, soil microbial communities, sorptivity, and wind and water erosion potential under continuous corn managed with two irrigation (full and limited) and two tillage (no‐till and strip till) levels after 3 yr on a silt loam in the central Great Plains. On average, residue removal was 66% for baling and 24% for grazing. Baling reduced SOC stocks by 2.16 Mg ha –1 yr –1 for the 0‐ to 20‐cm depth compared with no residue removal, but residue grazing, irrigation, and tillage had no effects. Full irrigation decreased mean weight diameter (MWD) of wet aggregates by 19% compared with limited irrigation, attributed to Na accumulation. No‐till had lower wind‐erodible fraction and greater microbial biomass than strip till. Regardless of irrigation and tillage, baling increased wind‐erodible fraction by 43% and decreased MWD by 56%, POM concentration by 41%, sorptivity by 57%, and microbial biomass in the upper 5‐cm depth compared with grazing and no residue removal. Grazing increased POM concentration and actinomycete biomass compared with no residue removal. Overall, changes in soil properties due to baling were larger and more rapid than in most previous studies, while grazing had fewer effects on soil properties.